2019
DOI: 10.1002/eco.2081
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall partitioning varies across a forest age chronosequence in the southernAppalachianMountains

Abstract: Evaporation of precipitation from plant surfaces, or interception, is a major component of the global water budget. Interception has been measured and/or modelled across a wide variety of forest types; however, most studies have focused on mature, second-growth forests, and few studies have examined interception processes across forest age classes. We present data on two components of interception, total canopy interception (E i ) and litter interception-that is, O i + O e horizon layers-(E ff ), across a fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 55 publications
(101 reference statements)
1
17
0
Order By: Relevance
“…We found that throughfall decreased while the canopy interception increased with increasing age, this pattern was in accordance with conifer species rainfall partitioning trend from young to adult in temperate boreal forests [13] and with deciduous forest A. altissima [31]. The study on a series of succession stands of Liriodendron tulipifera forest in the southern Appalachian Mountains also found that canopy interception increased rapidly with the forest age until reaching a maximum of 21% [27]. Another study on different Chinese fir stand ages got the similar trend that interception ratio in mature stands significantly higher [29].…”
Section: Age Dependence Of Rainfall Partitioningsupporting
confidence: 81%
“…We found that throughfall decreased while the canopy interception increased with increasing age, this pattern was in accordance with conifer species rainfall partitioning trend from young to adult in temperate boreal forests [13] and with deciduous forest A. altissima [31]. The study on a series of succession stands of Liriodendron tulipifera forest in the southern Appalachian Mountains also found that canopy interception increased rapidly with the forest age until reaching a maximum of 21% [27]. Another study on different Chinese fir stand ages got the similar trend that interception ratio in mature stands significantly higher [29].…”
Section: Age Dependence Of Rainfall Partitioningsupporting
confidence: 81%
“…Almost all precipitation ends up as throughfall in these young forests, as canopy interception is low (Brantley et al 2019). In the final year, some larger trees grew above the treatment panels, but changes to the treatment effect should have been minimal, because canopy interception for trees of this age is low (Brantley et al 2019). The 2013 growing season had 26% higher precipitation than the long-term average, while 2014 and 2015 were near average (7% and 0% higher, respectively; Miniat et al 2017).…”
Section: Experimental Designmentioning
confidence: 97%
“…Almost all precipitation ends up as throughfall in these young forests, as canopy interception is low (Brantley et al 2019). Almost all precipitation ends up as throughfall in these young forests, as canopy interception is low (Brantley et al 2019).…”
Section: Experimental Designmentioning
confidence: 98%
See 2 more Smart Citations